Why do we use different types of websites and assign them different levels of credibility? Structural relations among users' motives, types of websites, information credibility, and trust in the press. (January 2016) - Go, Eun; You, Kyung Han; Jung, Eunhwa; Shim, Hongjin
Abstract: The phenomenal growth in the use of the Internet as an information source has raised questions among scholars about why and how individuals use this resource. Based on uses and gratifications theory, the current study explored structural relations among individuals' specific motivations for using the Internet, their specific use of the web, credibility perceptions of online information and trust in the press using structural equation modeling method (N = 996). Consistent with our predictions, the distinct motivations (i.e., information seeking, social utility, and entertainment) were associated with the use of web portals, news websites, and social networking sites, respectively. Our findings also indicated that the use of news websites particularly influences users' perceptions of the credibility of online information as well as trust in the press. Furthermore, a significant association between credibility perceptions of online information and trust in the press was revealed. The implications of these findings are discussed. Highlights: Three motives led to individuals' online-media use, but the effects were varied. New websites use enhanced outcome variables, whereas SNS use lessened trust in the press. News websites use mediated the relation between motives and outcome variables.